Cerebrospinal fluid dynamics between the basal cisterns and the subarachnoid space of the optic nerve in patients with papilloedema. Issue 6 (17th October 2010) - Killer, Hanspeter Esriel; Jaggi, Gregor Peter; Miller, Neil R; Huber, Andreas R; Landolt, Hans; Mironov, Angel; Meyer, Peter; Remonda, Luca
Abstract : Aims: To determine cerebrospinal fluid (CSF) dynamics between intracranial CSF spaces and CSF in the subarachnoid space (SAS) of optic nerves (ONs) in 10 patients with papilloedema. Methods: Prospective assessment of 10 patients with papilloedema and two control subjects using CT cisternography and analysis of CSF for the presence of lipocalin-like prostaglandin D synthase (betatrace protein). Results: CT cisternography showed a progressively reduced influx of contrast-loaded CSF from intracranial CSF spaces into the SAS. The lowest concentration of contrast-loaded CSF was found in the region of the ON immediately behind the globe, where the ON sheath was widened (possibly by unfolding) in all patients compared with normal subjects. The concentration of lipocalin-like prostaglandin D synthase differed between the spinal CSF and the CSF in the SAS, with a markedly higher concentration in the SAS. Conclusion: The results of this study suggest that CSF turnover in the SAS of the ON is reduced in patients with papilloedema from various causes and that the composition of CSF differs between spinal CSF and that surrounding the ON.